(3GfTQGM GdUOQ aj HjGf djdI GdbOQs - (3eMeO Hf eMeO GdGejQ Hf MHjH Hf GdeNJGQ, CHh YHO Gddgs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd dcd TF bOQ hCfRd GdbQBf QMeI hTaGGeG HYO ajbhd GdabjQ GdCejQgP eG jSQg Gddg di s
(3BNQgG (B:s
(3cGf cef GOQc djdI GdbOQ ajfHZi GdCJjGf HPdc cd djdI hfSCd Gddg JYGdi ef cQeg GdYah hGdYGajI Je HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3jdjgG ETQGb GdHOQ ai HjGf aVGFd djdI GdbOQ ddYdGeI CHj GdUaG eMeO Hf Ydi GdRjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B307s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs